Climate Change and Journalism Negotiating Rifts of Time - Morris, Hanna E.; Bødker, Henrik (2021)
This edited collection addresses climate change journalism from the perspective of temporality, showcasing how various time scales-from geology, meteorology, politics, journalism, and lived cultures-interact with journalism around the world.Analyzing the meetings of and schisms between various temporalities as they emerge from reporting on climate change globally, Climate Change and Journalism: Negotiating Rifts of Time asks how climate change as a temporal process gets inscribed within the temporalities of journalism. The overarching question of climate change journalism and its relationship to temporality is considered through the themes of environmental justice and slow violence, editorial interventions, ecological loss, and political and religious contexts, which are in turn explored through a selection of case studies from the US, France, Thailand, Brazil, Australia, Spain, Mexico, Canada, and the UK.This is an insightful resource for students and scholars in the fields of journalism, media studies, environmental communication, and communications generally.